Adjuvant therapy in renal cell carcinoma: does higher risk for recurrence improve the chance for success?. (24th November 2017) - Figlin, R A; Leibovich, B C; Stewart, G D; Negrier, S
Abstract: The success of targeted therapies, including inhibitors of the vascular endothelial growth factor pathway or the mammalian target of rapamycin, in the treatment of metastatic renal cell carcinoma led to interest in testing their efficacy in the adjuvant setting. Results from the first trials are now available, with other studies due to report imminently. This review provides an overview of adjuvant targeted therapy in renal cell carcinoma, including interpretation of currently available conflicting data and future direction of research. We discuss the key differences between the completed targeted therapy adjuvant trials, and highlight the importance of accurately identifying patients who are likely to benefit from adjuvant treatment. We also consider reasons why blinded independent radiology review and treatment dose may prove critical for adjuvant treatment success. The implications of using disease-free survival as a surrogate end point for overall survival from the patient perspective and measurement of health benefit have recently been brought into focus and are discussed. Finally, we discuss how the ongoing adjuvant trials with targeted therapies and checkpoint inhibitors may improve our understanding and ability to prevent tumor recurrence after nephrectomy in the future.